2021
DOI: 10.3390/foods10102248
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Extraction Influence Protein Profiling of Edible Bird’s Nest

Abstract: The edible bird nest (EBN) from Aerodramus fuciphagus has been consumed as a Chinese traditional food for health and medicinal purposes due to its elevated nutritional value. The present study focused on the influence of characterization and extraction methods on protein profiling, which could be a guideline for grading the EBN. The proposed extraction method is similar to the common food preparation methods of consumers and thus can accurately establish the bioactive protein available upon human consumption. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…1 ), EBN was detected as a smear, distributed from more than 250 kDa down to approximately 10 kDa, suggesting a diversity of proteins present in EBN. In addition, thick bands showed up from 34 to 250 kDa in which bands in the molecular weight ranges of 95–130 kDa were described as sialic acid-binding glycoprotein [ 37 ]. After the treatment with fruit juices (juice to substrate ratio of 2.5:2 v/w), papain (enzyme to substrate ratio of 1.25:2 w/w), and bromelain (enzyme to substrate ratio of 0.625:2 w/w), large and complex proteins were hydrolyzed into smaller molecules as indicated by the faint high-molecular-weight bands at more than 34 kDa and the appearance of low-molecular-weight bands, especially bands in 17–26 kDa and 4.6–10 kDa ranges.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ), EBN was detected as a smear, distributed from more than 250 kDa down to approximately 10 kDa, suggesting a diversity of proteins present in EBN. In addition, thick bands showed up from 34 to 250 kDa in which bands in the molecular weight ranges of 95–130 kDa were described as sialic acid-binding glycoprotein [ 37 ]. After the treatment with fruit juices (juice to substrate ratio of 2.5:2 v/w), papain (enzyme to substrate ratio of 1.25:2 w/w), and bromelain (enzyme to substrate ratio of 0.625:2 w/w), large and complex proteins were hydrolyzed into smaller molecules as indicated by the faint high-molecular-weight bands at more than 34 kDa and the appearance of low-molecular-weight bands, especially bands in 17–26 kDa and 4.6–10 kDa ranges.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that enzymatic hydrolysis might influence the distribution of hydrophobic and hydrophilic amino acids on the surface, the protein-water interaction, and eventually increase the protein solubility. As soluble proteins and peptides are well-digested and quickly absorbed by the human body, EBN hydrolysates were much favored by athletes or digestive-impaired persons [ 37 ]. Therefore, our hydrolysates produced by fruit juices hold a promise in application due to the convenience and availability of fruits as compared to commercial enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Basically, FTIR spectra have been employed for rapid determination of B nest (Guo et al ., 2017). In addition, the evaluation of house‐B nest with different types (half cup and stripe‐shaped) was achieved using FTIR spectra (Mohamad Nasir et al ., 2021). Difference in FTIR spectra between house‐B nest and cave‐B nest might be governed by components or the interaction between components or functional groups in the nests.…”
Section: Resultsmentioning
confidence: 99%
“…Aqueous extracts are EBN extracts obtained by heating/boiling raw materials (RUC EBN/RC EBN/EBN by-products). Previous studies reported that protein solubility, degree of hydrolysis (DH), antioxidant activity, SA, and peptide content of EBN were positively correlated with heating time and temperature (Dai et al, 2022;Hun et al, 2015;Nasir et al, 2021;Ramachandran et al, 2017). Therefore, heating time and temperature will affect the extraction efficiency of EBN.…”
Section: Introductionmentioning
confidence: 99%